Neutron-converter backfills for microstructured semiconductor neutron detectors - Watson, Daniel (Kansas State University, 2023)
Micro-structured Semiconductor Neutron Detectors (MSNDs) emerged in the 2010s as a commercially available neutron detector with ideal size, weight, and power (SWAP) traits and inherently high gamma rejection ratios. The MSND technology was repurposed with double-sided devices (DS-MSNDs) and pixelated imaging devices of both single- and double-sided variants (X-MSND and X-DSMND). The upper limit of neutron detection efficiency with this technology is constrained by both the microstructure geometries of the semiconductor diodes and the properties of the neutron-reactive backfill. Methods to increase the packing fraction of 6LiF were investigated, leading to a sonic-tamping process regularly achieving >40% packing fraction results. Backfilled wafers were inspected for damage with leakage current measurements and showed no significant deterioration from the weighted-sonicated process. Parallel investigations sought to use alternative materials and methods to backfill neutron converter materials. Solvents of lithium fluoride were identified and their capabilities to dissolve and precipitate lithium fluoride showed no success, indicating previous publications instead observed surfactant-like behaviors. Efforts to backfill metallic lithium within the trenches revealed that low thermal contraction lithium-passivation conformal coatings would need to be applied to the silicon microstructured diodes before filling. The synthesis of lithium hydroxide during successive heated aqueous particle washing cycles was revealed, and a particle treatment process was conceived, producing microparticulate 6LiF optimized for mechanical backfilling with high measured zeta potential and low agglomeration. Finally, lithium peroxide was investigated as an alternative backfill due to the high atomic density of lithium; methods indicated that solvent-driven precipitation within the devices could yield packing fractions above 15% for this material.
Keywords: Neutron-converter MSND Backfill